2021
DOI: 10.1002/jcla.24094
|View full text |Cite
|
Sign up to set email alerts
|

The role of ferroptosis‐related genes for overall survival prediction in breast cancer

Abstract: Background Ferroptosis is a novel iron‐dependent form of cell death, which is implicated in various diseases including cancers. However, the influence of ferroptosis‐related genes on the prognosis of breast cancer remains unclear. Methods RNA sequencing data of 1053 breast cancer tissue samples and 111 normal tissue samples from The Cancer Genome Atlas (TCGA) were analyzed. Expression levels of 259 ferroptosis‐related genes were compared. Gene Ontology (GO) and the Kyoto Gene and Genomic Encyclopedia (KEGG) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
(54 reference statements)
1
7
0
Order By: Relevance
“…Multiple lines of evidence have suggested ferroptosis’ pivotal role in tumor suppressor pathways, including p53 activation, highlighting its relevance in the field of antineoplastic therapies [ 5 , 6 ]. Indeed, several studies have demonstrated the high potential of ferroptosis as a novel therapeutic strategy for the treatment of different cancers, including hepatic, lung and breast cancer [ 7 , 8 , 9 , 10 , 11 , 12 ]. Recent studies have confirmed that female breast cancer (BC) has overtaken lung cancer as the most commonly diagnosed cancer, with an estimated 2.3 million new cases (11.7%), closely followed by lung (11.4%), colorectal (10.0%), prostate (7.3%) and stomach (5.6%) cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple lines of evidence have suggested ferroptosis’ pivotal role in tumor suppressor pathways, including p53 activation, highlighting its relevance in the field of antineoplastic therapies [ 5 , 6 ]. Indeed, several studies have demonstrated the high potential of ferroptosis as a novel therapeutic strategy for the treatment of different cancers, including hepatic, lung and breast cancer [ 7 , 8 , 9 , 10 , 11 , 12 ]. Recent studies have confirmed that female breast cancer (BC) has overtaken lung cancer as the most commonly diagnosed cancer, with an estimated 2.3 million new cases (11.7%), closely followed by lung (11.4%), colorectal (10.0%), prostate (7.3%) and stomach (5.6%) cancers.…”
Section: Introductionmentioning
confidence: 99%
“…GO analysis can identify gene sets enriched in any of two groups, comparing one against the other but is almost always performed between tumor and normal tissue samples in order to find biological functions altered in tumors compared to healthy tissues [ 56 , 57 , 58 ]. In order to better characterize the tumor microenvironment, we extended that use to also identify the biological functions significantly altered in PP compared to GP samples.…”
Section: Discussionmentioning
confidence: 99%
“…Iron metabolism has also emerged as the possible therapeutic target and prognostic marker for breast cancer. Nowadays, the model based on ferroptosis-related genes in breast cancer has been found to be established in many studies [18][19][20], and the iron metabolism signature has been employed in lung adenocarcinoma, glioma, clear cell renal cell carcinoma, and hepatocellular carcinoma [21][22][23][24]. However, prognostic value and therapeutic importance of iron metabolismrelated genes in breast cancer remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, targeting iron metabolism-related proteins has been developed into a promising avenue of cancer therapy, which could exert antitumor effects by enhancing antitumor immunity. Nowadays, the models based on ferroptosis-related genes in breast cancer have been established in many studies [18][19][20], and the signatures related to iron metabolism have been used in lung adenocarcinoma, glioma, renal cell carcinoma, hepatocellular carcinoma [21][22][23][24]. However, a comprehensive analysis of prognostic value and therapeutic signi cance of iron metabolism related genes in breast cancer was still unclear.…”
Section: Introductionmentioning
confidence: 99%